The First Mom And Dad - Dania, Deji (Literamed Publications Nigeria Limited, 2009)
God warned the first Mom and Dad against eating the fruit of the tree of The Knowledge of Good and Evil,but the serpent comes around,and a happy existence turns sour.
Keywords: Christianity; Bible Stories; Religion